Heart rate lowering treatment leads to a reduction in vulnerable plaque features in atherosclerotic rabbits. - Raf H M van Hoof; Evelien Hermeling; Judith C Sluimer; Julie Salzmann; Arnold P G Hoeks; Jérôme Roussel; Mat J A P Daemen; Harry Struijker-Boudier; Joachim E Wildberger; Sylvia Heeneman; M Eline Kooi (PLoS ONE, 2017)
Objective To investigate the effect of a heart rate (HR) lowering agent (Ivabradine) on features of atherosclerotic plaque vulnerability with magnetic resonance imaging (MRI), ultrasound imaging, and histology. Approach and results Atherosclerosis was induced in the abdominal aorta of 19 rabbits. Nine rabbits were treated with Ivabradine (17 mg/kg/day) during the entire study period. At week 14, imaging was performed. Plaque size was quantified on contrast-enhanced T1-weighted MR images. Microvascular flow, density, and permeability was studied with dynamic contrast-enhanced MRI. Plaque biomechanics was studied by measuring the aortic distension with ultrasound. After, animals were sacrificed and histology was performed. HR was reduced by 16% (p = 0.026) in Ivabradine-treated animals. No differences in absolute and relative vessel wall beat-to-beat distension were found, but due to the reduction in HR, the frequency of the biomechanical load on the plaque was reduced. Plaque size (MR and histology) was similar between groups. Although microvessel density (histology) was similar between groups, AUC and Ktrans, indicative for plaque microvasculature flow, density, and permeability, were decreased by 24% (p = 0.029) and 32% (p = 0.037), respectively. Macrophage content (relative RAM11 positive area) was reduced by 44% (p<0.001) on histology in Ivabradine-treated animals. Conclusions HR lowering treatment with Ivabradine in an atherosclerotic rabbit model is associated with a reduction in vulnerable plaque features. The current study suggests that HR reduction may be beneficial for inducing or maintaining a more stable plaque phenotype.